A GENDER PERSPECTIVE ON COHESIV DEVICES IN NARRATIVE WRITING OF SBI EKA ENGLISH COURSE PASIRIAN STUDENTS - SUDIRMAN, FITRI ANJARSARI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Narrative is one kind of popular writing. Therefore, students have to consider the cohesion and coherence of their writing. In creating coherent writing papers, cohesive devices has significant role because they provide not only surface evidence for the text unity but also express the continuity that exist between one part of the text and another. However, some studies show that male and female have different style in using language. Thus, the writer is interested in investigating the cohesive devices used in narrative written by male and female students. The problems are (1) What are the types of cohesive devices used by male and female students in their narrative writing? and (2) how do cohesive devices help a coherence of their paragraphs?    This study is a descriptive qualitative study. The data of this study are cohesive devices taken from 6 narrative writings written by SBI EKA English Course Pasirian Students. All of the narrative writings are going to be analyzed based on Halliday and Hasan’s theory of cohesive devices.     The result of this study shows that male students use 61.31% grammatical cohesive devices and 38.68% lexical cohesive devices. Meanwhile, female students use 68.67% grammatical cohesive devices and 31.32% lexical cohesive devices. It can be concluded that male students use lexical cohesive devices in higher percentage rather than female, while female students use grammatical cohesive devices in higher percentage than male. The differences are found in terms of grammatical cohesive devices used. Substitution is only found in female students’ narrative writings, while no male student uses it. Ellipsis is only found in male student’s narrative writing, while no female uses it.     From the result, it can be concluded that cohesive devices have important implications for understanding the role of coherence in writing quality. It is expected that this research is useful for the teachers, students, and any other professions who have intension to produce more qualified and rationale text of speech which can achieve their aim.Key words : cohesive devices, coherence, narrative writing, male and female students.